Past and present "urban voids" as resources for the future. The case-study of Catania - Caterina Cirelli; Leonardo Mercatanti; Cormelo Maria Porto (European Regional Science Association (ERSA), 2002)
Since the end of the 1960s, the landscapes of major cities have been more and more characterized by the presence of "urban voids". Today these "voids", which are often heterogeneous in their manifestation, dominate the discussions about the transformation and the future of urban areas. The reclaiming and re-use of derelict sites and "cultural heritage" has the duty to assure for the next generation the knowledge of the cultural values of the past. In this paper we will focus our attention on a re-used "cultural heritage": the Multifunctional Centre of Catania (Sicily, Objective 1 region). Thanks to the Urban Programme this "urban void"- abandoned for decades and deteriorated - was recovered and is now a library and lecture rooms complex of the University of Catania. We will discuss the complex structural actions realized inside this building, which contains the memory of the values and culture of the harbour area of Catania, and its new functional aspects.
Keywords: 330